2021
DOI: 10.3390/ani11051450
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Black Soldier Fly Ingredient on the Growth Performance and Disease Resistance of Juvenile Pacific White Shrimp (Litopenaeus vannamei)

Abstract: This study was performed as part of developing a functional feed ingredient for juvenile Pacific white shrimp (Litopenaeus vannamei). Here we assess the effects of dietary inclusion of a Black Soldier Fly Ingredient (BSFI) from defatted black soldier fly (Hermetia illucens) larvae meal on growth performance, tolerance to salinity stress, and disease resistance when challenged with Vibrio parahaemolyticus or a strain of white spot syndrome virus (WSSV). A control diet was used for comparison with three test die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 48 publications
(65 reference statements)
1
29
0
Order By: Relevance
“…Insects such as the BSF have been extensively studied, not only in fish culture but also in poultry and swine ( Sogari et al., 2019 ). In aquaculture, many studies have revealed positive results when BSF meal was used as a substitute for fish meal for many species such as whiteleg shrimp ( Litopenaeus vannamei ) ( Richardson et al., 2021 ), barramundi ( Lates calcarifer ) ( Hender et al, 2021 ), climbing perch ( Anabas testudineus ) ( Mapanao et al., 2021 ), Nile tilapia ( Oreochromis niloticus ) ( Were et al., 2021 ), African catfish ( Clarias gariepinus ) ( Fawole et al., 2020 ), Japanese sea bass ( Lateolabrax japonicus ) ( Wang et al., 2019 ), Atlantic salmon ( Salmo salar ) ( Lock et al, 2016 ; Stenberg et al., 2019 ), Siberian sturgeon ( Acipenser baerii ) ( Zarantoniello et al, 2021 ), gilthead sea bream ( Sparus aurata ) ( Randazzo et al, 2021 ), clownfish ( Amphiprion ocellaris ) ( Vargas-Abúndez et al, 2019 ) and in rainbow trout ( Oncorhynchus mykiss ) ( Cardinaletti et al., 2019 ) to produce food fish. In the aforementioned species, BSF improved various growth parameters as well as the immune response to some diseases affecting aquatic species.…”
Section: Insect Species Utilized In Aquafeedmentioning
confidence: 99%
See 2 more Smart Citations
“…Insects such as the BSF have been extensively studied, not only in fish culture but also in poultry and swine ( Sogari et al., 2019 ). In aquaculture, many studies have revealed positive results when BSF meal was used as a substitute for fish meal for many species such as whiteleg shrimp ( Litopenaeus vannamei ) ( Richardson et al., 2021 ), barramundi ( Lates calcarifer ) ( Hender et al, 2021 ), climbing perch ( Anabas testudineus ) ( Mapanao et al., 2021 ), Nile tilapia ( Oreochromis niloticus ) ( Were et al., 2021 ), African catfish ( Clarias gariepinus ) ( Fawole et al., 2020 ), Japanese sea bass ( Lateolabrax japonicus ) ( Wang et al., 2019 ), Atlantic salmon ( Salmo salar ) ( Lock et al, 2016 ; Stenberg et al., 2019 ), Siberian sturgeon ( Acipenser baerii ) ( Zarantoniello et al, 2021 ), gilthead sea bream ( Sparus aurata ) ( Randazzo et al, 2021 ), clownfish ( Amphiprion ocellaris ) ( Vargas-Abúndez et al, 2019 ) and in rainbow trout ( Oncorhynchus mykiss ) ( Cardinaletti et al., 2019 ) to produce food fish. In the aforementioned species, BSF improved various growth parameters as well as the immune response to some diseases affecting aquatic species.…”
Section: Insect Species Utilized In Aquafeedmentioning
confidence: 99%
“…(2019) Meal Rainbow trout 137.0 ± 10.50 98 d 50 Activation of immune related genes such as interleukin 10 (IL-10), TNF- α and toll-like receptor 5 (TLR-5) Cardinaletti et al. (2019) Meal Pacific white shrimp ( Litopenaeus vannamei ) 0.67 ± 0.15 4 wk 7.5 Improved weight gain, feed conversion ratio (FCR) and specific growth rate (SGR) Richardson et al. (2021) Meal Barramundi ( Lates calcarifer ) 1.74 ± 0.15 42 d 30 Improved growth and feed utilization, bactericidal activity and upregulation of immune-related genes such as interleukin 1 (IL-1) and IL-10 Hender et al (2021) Oil Barramundi 1.74 ± 0.15 42 d 30 Enhanced growth performance and upregulation of immune-related genes (IL-1 and IL-10) Hender et al (2021) Partially defatted meal Rainbow trout 178.9 ± 9.81 78 d 50 Sensitivity and modulation of intestinal bacterial community and structure.…”
Section: Utilization In Aquafeedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, insects have been recognized as one of the most potent alternative protein sources for animal feeds, mainly due to their high nutritional composition, easy production, rapid growth, short reproductive cycle, high feed conversion efficiency, and low production cost [ 18 , 22 , 23 , 24 , 25 , 26 ]. Several studies on the potential usage of insects, such as black soldier fly larvae, house fly maggots, mealworms, grasshoppers, crickets, and silkworm meal, as FM replacements have been reported [ 24 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salinity variation is a controllable way of generating stress in the organisms, and their response can be evaluated, thus indirectly providing information about their physiological status. Healthy shrimp can tolerate a wide variation in salinity (Richardson et al 2021). The concentration of BA in muscle was evaluated, and specific analyses that were focused on the hepatopancreas, such as the hepatosomatic index (HSI), determination of lipids, and histopathological analyses, were conducted to identify where and how BA affected Pacific white shrimp juveniles and to evaluate whether energy and lipids would be used for survival purposes rather than growth.…”
mentioning
confidence: 99%